1998
DOI: 10.1021/jp982286o
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Chemistry of 1,3-Dienes on the Silicon(001) Surface:  Competition between [4 + 2] and [2 + 2] Reactions

Abstract: The reactions of 1,3-dienes with the Si(001) surface have been investigated using scanning tunneling microscopy (STM) and Fourier transform infrared spectroscopy (FTIR), and the relative efficiencies of [2 + 2] and [4 + 2] reactions have been determined. STM and FTIR studies show that the 2,3-dimethyl-1,3-butadiene molecule has two bonding configurations; 80% of the molecules bond via a [4 + 2] reaction involving both alkene groups with the remaining 20% bonding via a [2 + 2] reaction involving only one alkene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
153
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(162 citation statements)
references
References 35 publications
9
153
0
Order By: Relevance
“…13 The addition of 2,3-dimethyl-1,3-butadiene to Si(100) was also explored by Hamers and co-workers. 19 The surface species were found to comprise 80% of the Diels-Alder product, with the remaining 20% arising from a [2+2] addition. Okamura et al 20 used IR spectroscopy to investigate the adsorption of naphthalene on Si(100).…”
Section: Introductionmentioning
confidence: 99%
“…13 The addition of 2,3-dimethyl-1,3-butadiene to Si(100) was also explored by Hamers and co-workers. 19 The surface species were found to comprise 80% of the Diels-Alder product, with the remaining 20% arising from a [2+2] addition. Okamura et al 20 used IR spectroscopy to investigate the adsorption of naphthalene on Si(100).…”
Section: Introductionmentioning
confidence: 99%
“…This asymmetric approach is of lower symmetry and can occur with a lower energy barrier. Conjugated dienes or multienes [21][22][23][24] can be covalently bonded to Si(100)-2ϫ1 through ͓4ϩ2͔-like or/and ͓2ϩ2͔-like cycloaddition strategies. For six-membered aromatic molecules and their substitutions, [25][26][27][28][29][30][31][32][33][34] their binding mechanisms are…”
Section: Introductionmentioning
confidence: 99%
“…The (2ϫ1) surface reconstruction obtained by a simple lateral translation of surface Si-atoms to form Si dimers was first suggested by Schlier and Farnsworth 2 in 1959 and further confirmed in the scanning tunneling microscopic ͑STM͒ studies by Hamers et al [3][4][5] Many of the physical and chemical properties of Si͑100͒ can be rationalized by considering a double bond feature of dimer, that is, a strong bond linking the two Si atoms and a rather weak bond. All studies of simple alkenes on Si͑100͒ have shown a facial ͓2ϩ2͔ cycloaddition reaction pathway; [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] despite the fact that, according to Woodward's rule, the analogous reaction of two organic alkenes is forbidden in the high-symmetry suprafacial-suprafacial ͓2 s ϩ2 s ͔ approach. 23 Moreover, experimental evidence has shown that the molecular stereochemistry is preserved through this reaction, thereby ruling out the suprafacialantarafacial ͓2 s ϩ2 a ͔ mechanism.…”
Section: Introductionmentioning
confidence: 99%